628 Management of Chyle Leaks Following Oesophagectomy: A Systematic Review. (12th October 2021) - Power, R; Smyth, P; Donlon, N E; Nugent, T; Donohoe, C L; Reynolds, J V
Abstract: Aim: Chyle leakage is a rare but potentially life-threatening complication following oesophageal resection. The optimal management strategy is not clear. Method: Searches were conducted up to 31/12/2020 on MEDLINE, Embase and Web of Science for randomised trials or retrospective studies that evaluated the management of chyle leakage following oesophageal resection. Two authors independently screened studies extracted data and assessed for bias. The protocol was prospectively registered on PROSPERO (CRD: 42021224895) and reported in accordance with PRISMA guidelines. Results: A total of 530 citations were reviewed. Twenty-five studies, totaling 1016 patients met the inclusion criteria, including 2 low-quality clinical trials and 23 retrospective case series. Heterogeneity of study design and outcomes prevented meta-analysis. The overall incidence of chyle leaks was 3.2% but no consistent risk factors were found across studies. Eighteen studies describe management of chyle leaks conservatively, 17 by surgical ligation of the thoracic duct, and 6 described percutaneous lymphangiography with thoracic duct embolisation (TDE) or disruption (TDD). There is a paucity of high-quality prospective studies directly comparing treatment modalities, but there is some low-certainty evidence that percutaneous approaches have reduced morbidity, but lower efficacy compared to surgery. Conclusions: The evidence-base for optimal management of chyle leakage post-oesophagectomy is lacking, which may be related to its low incidence. Further high quality, prospective studies that compare interventions at different levels of severity are needed to determine the optimal approach to treatment.